Effects of Nicotine on the Neurophysiological and Behavioral Effects of Ketamine in Humans - Mathalon, Daniel H.; Ahn, Kyung-Heup; Perry, Edward; Cho, Hyun-Sang; Roach, Brian J.; Blais, Rebecca; Bhakta, Savita; Ranganathan, Mohini; Ford, Judith M.; D'Souza, Deepak C. (Frontiers in Psychiatry, 2014)
Background: N-methyl-D-aspartate (NMDA) receptor hypofunction has been implicated in the pathophysiology of schizophrenia and its associated neurocognitive impairments. The high rate of cigarette smoking in schizophrenia raises questions about how nicotine modulates putative NMDA receptor hypofunction in the illness. Accordingly, we examined the modulatory effects of brain nicotinic acetylcholine receptor (nAChR) stimulation on NMDA receptor hypofunction by examining the interactive effects of nicotine, a nAChR agonist, and ketamine, a noncompetitive NMDA receptor antagonist, on behavioral and neurophysiological measures in healthy human volunteers. Methods: From an initial sample of 17 subjects (age range 18 - 55 years), 8 subjects successfully completed 4 test sessions, each separated by at least 3 days, during which they received ketamine or placebo and two injections of nicotine or placebo in a double-blind, counterbalanced manner. Schizophrenia-like effects (PANSS), perceptual alterations (CADSS), subjective effects (VAS) and auditory event-related brain potentials (mismatch negativity, P300) were assessed during each test session. Results: Consistent with existing studies, ketamine induced transient schizophrenia-like behavioral effects. P300 was reduced and delayed by ketamine regardless of whether it was elicited by a target or novel stimulus, while nicotine only reduced the amplitude of P3a. Nicotine did not rescue P300 from the effects of ketamine; the interactions of ketamine and nicotine were not significant. While nicotine significantly reduced MMN amplitude, ketamine did not. Conclusion: Nicotine failed to modulate ketamine-induced schizophrenia-like effects in this preliminary study. Interestingly, ketamine reduced P3b amplitude and nicotine reduced P3a amplitude, suggesting independent roles of NMDA receptor and nAChR in the generation of P3b and P3a, respectively.